Moving Health Upstream in Urban Development: Reflections on the Operationalization of a Transdisciplinary Case Study. Issue 4 (7th August 2018) - Black, Daniel; Scally, Gabriel; Orme, Judy; Hunt, Alistair; Pilkington, Paul; Lawrence, Roderick; Ebi, Kristie
Abstract: This paper describes the development, conceptualization, and implementation of a transdisciplinary research pilot, the aim of which is to understand how human and planetary health could become a priority for those who control the urban development process. Key challenges include a significant dislocation between academia and the real world, alongside systemic failures in valuation and assessment mechanisms. The National Institutes of Health four‐phase model of transdisciplinary team‐based research is drawn on and adapted to reflect on what has worked well and what has not operationally. Results underscore the need for experienced academics open to new collaborations and ways of working; clarity of leadership without compromising exploration; clarification of the poorly understood "impacts interface" and navigation toward effective real world impact; acknowledgement of the additional time and resource required for transdisciplinary research and "nonacademic" researchers. Having practitioner‐researchers as part of the research leadership team requires rigourous reflective practice and effective management, but it can also ensure breadth in transdisciplinary outlook as well as constant course correction toward real‐world impact. It is important for the research community to understand better the opportunities and limitations provided by knowledge intermediaries in terms of function, specialism, and experience. Abstract : This paper describes the development, conceptualization, and implementation of a transdisciplinary research pilot, the aim of which is to understand how human and planetary health could become a priority for those who control urban development. It adapts the National Institutes of Health four‐phase model of transdisciplinary team‐based research to reflect on what has worked well and what has not operationally.